2019
DOI: 10.1093/toxsci/kfz251
|View full text |Cite
|
Sign up to set email alerts
|

A Novel, Modified Human Butyrylcholinesterase Catalytically Degrades the Chemical Warfare Nerve Agent, Sarin

Abstract: Chemical warfare nerve agents (CWNAs) present a global threat to both military and civilian populations. The acute toxicity of CWNAs stems from their ability to effectively inhibit acetylcholinesterase (AChE). This inhibition can lead to uncontrolled cholinergic cellular signaling, resulting in cholinergic crisis and, ultimately, death. Although the current FDA-approved standard of care is moderately effective when administered early, development of novel treatment strategies is necessary. Butyrylcholinesteras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…In 2019, McGarry et al 86 reported a phenomenon that the BChE of porcine could be self‐reactivated after being inhibited by sarin. Then they introduced four nonimmunogenic mutants into hu BChE to imitate the structure of porcine BChE, that is, hu BChE variant (Y282N/G283H/T284M/P285L) 87 . All of the mutants located near acyl‐binding pocket.…”
Section: The Role Of Bche In Detoxifying Opsmentioning
confidence: 99%
“…In 2019, McGarry et al 86 reported a phenomenon that the BChE of porcine could be self‐reactivated after being inhibited by sarin. Then they introduced four nonimmunogenic mutants into hu BChE to imitate the structure of porcine BChE, that is, hu BChE variant (Y282N/G283H/T284M/P285L) 87 . All of the mutants located near acyl‐binding pocket.…”
Section: The Role Of Bche In Detoxifying Opsmentioning
confidence: 99%